1969
DOI: 10.1099/00221287-55-3-351
|View full text |Cite
|
Sign up to set email alerts
|

The Coupling of Phosphate Accumulation to Acid Production by a Non-growing Streptococcus

Abstract: S U M M A R YAccumulation of phosphate by washed, stored suspensions of stationary phase streptococcal strain SL-I is strictly energy-dependent, essentially unidirectional and coupled stoichiometrically to acid production. At saturating concentrations of extracellular glucose and phosphate, incubation at varying pH values alters the rates of phosphate accumulation and concomitant fermentation of glucose such that coupling remains intact. Extracellular pH, while not affecting the coupling of phosphate accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

1974
1974
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…Inorganic phosphate has often been thought to be lost from plaque partly by uptake by microorganisms in metabolic phosphorylation reactions [Luoma, 1964;Tanzer et al, 1969]. While Dawes and Jenkins [1962] claimed that a sugar rinse decreases plaque P i , Tatevossian [1987] and Tatevossian and Jenkins [1969] were unable to consistently confirm this finding.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Inorganic phosphate has often been thought to be lost from plaque partly by uptake by microorganisms in metabolic phosphorylation reactions [Luoma, 1964;Tanzer et al, 1969]. While Dawes and Jenkins [1962] claimed that a sugar rinse decreases plaque P i , Tatevossian [1987] and Tatevossian and Jenkins [1969] were unable to consistently confirm this finding.…”
Section: Discussionmentioning
confidence: 63%
“…The effect of sugar on the inorganic orthophosphate (P i ) content of plaque is not so clear [Tatevossian et al, 1975;Ashley and Wilson, 1977a]. P i is taken up by fermenting cells and used in sug-ar phosphorylation and other anabolic processes [Luoma, 1964;Tanzer et al, 1969] and organic phosphate content may be slightly higher in plaque after extensive sugar exposure [Wilson and Ashley, 1988].…”
mentioning
confidence: 99%
“…Several investigators have noted the high uptake of phosphorus by cariogenic streptococci and the increase in uptake in the presence of sucrose. 85,86 Recently, Luoma87 showed that the source of the phosphorus could be tooth enamel. Bowden, Nash, and Speirs88 found that uptake of phosphorus was not only dependent on carbohydrate but on viability of the bacterial cells as well.…”
Section: Relation Of Salivary Proteins To Cariesmentioning
confidence: 99%
“…The rise in Ca 2z concentration in plaque¯uid when pH falls (4,5), possibly originating from cell wall-bound Ca (6) and/or plaque mineral deposits (7), would tend to counteract the effect of H z on apatite saturation. Phosphate and¯uoride levels in plaque¯uid, on the other hand, do not appear to change signi®cantly after sugar rinsing (8,9) and, while pHsensitive release mechanisms have been postulated (10,11), these effects may be more or less negated by simultaneous uptake by bacterial cells through metabolic phosphorylation reactions (12) and intracellular diffusion of HF (13).…”
mentioning
confidence: 95%